Comparación de Tres Métodos de Análisis de Variables Binarias - Montaldo, Hugo H. (Acta Universitaria, 2002)
This study compares lineal models (ML), contingency tables using Chisquare (TC) and logistic regression (RL) on their efficiency to test hypothesis about differences of percentages between two treatments. Efficiency was defined as the probability of not commit error type I. A series of simulated cases with 4 and 25 repetitions were analyzed. Considering the lower efficiency of ML, particularly with few replicates and the limitations of TC for the analysis of the binary variables, the results of this preliminary study show that in agreement with the theoretical expectations, the RL method, readily available in several tested programs of statistical software, should be prefered for the analysis of experiments with binary dependent variables.
Keywords: Array; Array; Array; Array